Tin-free radical mediated C-C bond formation via the Xanthate transfer - Goh, Kelvin Kau Kiat (2015)
Formation of carbon-carbon bonds had been by far the most researched and refined objective in organic synthesis. On the contrary, the use of free-radical chemistry in this area had thus been limited to tin-mediated protocols which were gradually losing popularity due to toxicity and purification issues. Xanthates, a class of thiocarbonylthio compounds have found remarkable application in both inter- and intra-molecular tin-free radical additions to simple and un-activated olefins. In this thesis, the use of xanthates is further explored and renewed through combination with other types of radical chemistry previously employed with tin-based initiators. The goal is to develop novel tin-free solutions in the C-C bond formation for the synthesis of highly functionalized molecules which had otherwise been plagued by acid-base problems in ionic chemistry. This concept is briefly demonstrated by a few free-radical alternatives to enolate chemistry involving ketones, lactones and thiolactones.